IMPLIKASI HAK KEPEMILIKAN DAN KONVERSI HUTAN RAKYAT: STUDI KASUS DAERAH TANGKAPAN AIR WADUK JATIGEDE - Nunung Parlinah; Bramasto Nugroho; Muhamad Buce Saleh; Hendrayanto Hendrayanto (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2020)
Small-scale forest as private property has implications on autonomous management decisions, including whether it will be preserved or converted. Changes in land management at the water catchment area of Jatigede reservoir will impact on the dam condition. The purposes of this study are to determine the financial feasibility level of the small-scale forest business compare to other forms of land management, to identify factors influencing farmer’s decisions, and to evaluate implication of property rights to the conversion of small-scale forest. The results show that small-scale forest management in Jatigede catchment area is generally found in the form of woodlands and agroforestry. Other forms of land management are rice fields and crops. Financial analysis shows that all land management patterns are feasible. The economic factors in the form of profits, savings, and selffulfillment are the dominant motivations for timber planting. The financial benefit difference between agroforestry and crops management is not very large, but the potential for conversion is still exists due to daily need fulfillment. One approach that can be applied to prevent small-scale forest conversion is through policy interventions on payment for environmental services, where the target is more intended for empowerment activities to meet the needs of daily living.